Rhino-Orbital Mucormycosis Associated With COVID-19 - Mehta, Salil (Cureus, 2020)
Coronavirus disease 2019 (COVID-19) infections may be associated with a wide range of bacterial and fungal co-infections. We report the case of a patient with COVID-19 infection, which, during the course of the treatment, developed rhino-orbital mucormycosis. A 60- year-old male patient, a longstanding diabetic, with a positive reverse-transcriptase polymerase chain reaction (RT-PCR) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was admitted for treatment. He received parenteral meropenem and oral oseltamivir with parenteral methylprednisolone. Over the course of the admission, he developed signs of orbital cellulitis. Magnetic resonance imaging (MRI) of the brain, orbits, and paranasal sinuses, revealed soft tissue swelling in the right preseptal, malar, premaxillary and retrobulbar regions with paranasal sinusitis. A nasal biopsy revealed broad aseptate filamentous fungal hyphae suggestive of mucormycosis, which was confirmed on culture. Extensive use of steroids/monoclonal antibodies/broad-spectrum antibiotics may lead to the development/exacerbation of a preexisting fungal disease. Physicians should be aware of the possibility of secondary invasive fungal infections in patients with COVID-19 infection.